Article Review: An Exploration of the Potential of Biochar-Based Bifunctional Catalysts as A Renewable Energy-Based Fuel Innovation - Tiara Ramadhani; Ahmad Nasir Pulungan; Salaisa Salaisa; Annisya Dwi Putri Zulmi; Muhammad Fatra Arganda Saragih; Sella Naomi Br Sinaga; Tesalonika Bela Simanjuntak (UIN Sulthan Thaha Saifuddin Jambi, 2024)
Palm oil shells, as biomass waste, have great potential to be used as raw material for biochar-based bifunctional catalysts. The aim of this research is to assess the potential of palm shell-based biochar as a bifunctional catalyst carrier in the conversion of biomass into renewable fuel. The method used is a literature review of various related articles, with a focus on the characteristics of biochar, the incorporation of bimetallic metals, and catalyst performance. The results of the discussion show that biochar from palm oil shells has textural properties that support the distribution of the catalyst metal, with a high surface area and optimal pore volume at a certain pyrolysis temperature. Incorporation of bimetallic metals on the biochar surface increases catalytic activity through synergy between metals, which has the potential to increase efficiency in catalytic reactions such as hydrogenation and deoxidation. In conclusion, palm shell-based biochar can be an effective and environmentally friendly alternative catalyst in converting biomass into renewable fuel, by selecting the right metal composition to optimize catalyst performance and prevent clumping of active components.